2022
DOI: 10.3390/nu14112249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Pepper (Piper nigrum) Extract on Caffeine-Induced Sleep Disruption and Excitation in Mice

Abstract: Sleep is one of the most essential factors required to maintain good health. However, the global prevalence of insomnia is increasing, and caffeine intake is a major trigger. The objective of this study was to investigate the inhibitory effect of black pepper, Piper nigrum extract (PE), on caffeine-induced sleep disruption and excitation in mice. Caffeine significantly decreased sleep duration in the pentobarbital-induced sleep test. It also resulted in a significant increase in sleep onset and a decrease in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The delta activity is used as a sleep parameter to evaluate sleep intensity in NREMS [ 43 , 44 ]. This study confirmed that caffeine did not change the delta activity [ 11 ] and that caffeine, as well as GT, induces arousal-inducing effects without a change in the delta activity. To evaluate whether GT presents withdrawal symptoms or adverse effects using EEG and EMG, recordings in withdrawal days were analyzed in the mice.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The delta activity is used as a sleep parameter to evaluate sleep intensity in NREMS [ 43 , 44 ]. This study confirmed that caffeine did not change the delta activity [ 11 ] and that caffeine, as well as GT, induces arousal-inducing effects without a change in the delta activity. To evaluate whether GT presents withdrawal symptoms or adverse effects using EEG and EMG, recordings in withdrawal days were analyzed in the mice.…”
Section: Discussionsupporting
confidence: 83%
“…The administration of caffeine significantly decreased the number of bouts of wakefulness ranging from 10 to 30 s during the 21 days ( Figure 6 b). However, a previous study reported that a significant decrease was not induced in the number of bouts of wakefulness ranging from 10 to 30 s [ 11 ]. Because we investigated the sleep-promoting effects of extract using the caffeine-induced sleep disruption model, our study was performed to evaluate the arousal-inducing effect of GT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep was evaluated based on the prolongation of the pentobarbital-induced sleeping time by the treatments. Sleep evaluation was performed between 10:00 and 16:00 as previously described [ 22 , 23 , 24 ] with slight modification. Two separate different doses of pentobarbital were used.…”
Section: Methodsmentioning
confidence: 99%
“…Reviews on the use of P. nigrum highlighted the in vivo neuroprotective and hypoglycemic effects presenting a potential for further research, especially to investigate its capacity to inhibit acetylcholinesterase and butyrylcholinesterase, two enzymes critically implicated in Alzheimer's and Parkinson's disorders, but also α-amylase, α-glucosidase, and lipase enzymes [6] as well as other neuroprotective properties reducing caffeineinduced effects on mice hyperlocomotion [7].…”
Section: Introductionmentioning
confidence: 99%